The Portrait of Social Media on Students’ Lifestyle and Education Culture - Sururin, Sururin; Nawawi, Mukhshon; Subchi, Imam; Amyn, Ilham Maulana (Universitas Islam Negeri Raden Intan Lampung, 2021)
Technological advancements bring about changes in people's lives, particularly in lifestyle and educational culture. This study aims to examine the impact of social media on the lifestyle and culture of IAIN Metro Lampung students. The sampling technique employed was random sampling which determined 147 students. A closed-ended questionnaire with a Likert scale was utilized as the instrument, then graded based on the percentage scale. The study reveals that social media has a varying degree of effects on IAIN Metro Lampung students' lifestyle and educational culture changes. The influence of social media, lifestyle, and educational culture has more than 10 percent. Social media presents both positive and harmful consequences. Recommendations for the next researcher are to investigate the overcome the negative impacts created by lifestyle and educational culture changes as the impacts of social media.